An insight into the air stability of the benchmark polymer:Fullerene photovoltaic films and devices: A comparative study - James McGettrick (Organic Electronics, 2020)
In this study, a comparative analysis of the instabilities and degradation routes of organic solar cell (OSCs) employing the three benchmarked donor polymers namely poly(3-hexylthiophene) (P3HT), poly[N-900- hepta-decanyl-2,7-carbazole-alt-5,5-(40,70-di-2-thienyl-20,10,30-benzothiadiazole)] (PCDTBT) and Poly[[4,8-bis[(2-ethylhexyl)oxy]benzo[1,2- b:4,5-b']dithiophene-2,6-diyl][3-fluoro-2-[(2 ethylhexyl)carbonyl] thieno[3,4-b]thiophenediyl]] (PTB7) along with [6,6]-phenylC71 butyric acid methyl-ester (PC71BM) acceptor have been conducted using the extracted photovoltaic parameters in conjunction with the X-ray photoelectron spectroscopy (XPS), optical and morphological analysis. During the 14 days air stability test, the power conversion efficiency (PCE) decreased by 78.85%, 65.83% and 83.36% for P3HT:PC71BM, PCDTBT:PC71BM and PTB7:PC71BM based devices, respectively. However, the degradation study of the bulk heterojunction (BHJ) films was prolonged to 28 days in order to further elucidate the degradation factors affecting the device performance. XPS, optical and morphological studies enabled detailed information on the device degradation mechanisms and confirmed the oxidation of photoactive layer after ageing, morphological deterioration and fall in absorbance, particularly, the PTB7:PC71BM blend that showed the rapid degradation among all three. The results obtained in the current study advance the understanding of the stability/degradation mechanisms pertaining to the three most commonly used BHJ materials and hence, will help to improve the OSCs for longer lifetime.